MANIFESTATION OF AIDS WITH DIARRHEA - Zainuddin, Rahmat; Nasronudin, Nasronudin (Indonesian Journal of Tropical and Infectious Disease, 2014)
Infectious diseases HIV/AIDS is a global health problem. According to WHO (2000) reported that 58 million people in the world are infected with HIV, within the 22 million people died from AIDS or 7000 people die every day. HIV Infection caused decrease and disorder of humoral and cellular immunity. Intestinal mucosal normally shows a physiologic inflamation that account for intestinal mucosal integrity. Diarhhea in HIV infection due to immune deficiency can caused by pathogen and non pathogen. Acute and chronic diarrhea usually found in HIV infection patient, the latter is more frequent. HIV enteropathy cause chronic diarrhea without pathogen infection because intestinal mucous damage by HIV direct infection. Treatment is characterized as causative supportive and symptomatic treatment causal, supportive and Symptomatic. Immunonutrient is very important within management patient HIV/AIDS.